Green Strategy, Eco-Efficiency, and Intellectual Capital: Empirical Study in Indonesia - Suwandi, Suwandi (AKRUAL: JURNAL AKUNTANSI, 2025)
Today, companies are not only responsible for a single bottom line, which is the value of the company reflected in economic conditions. However, companies must be responsible for triple bottom lines, including economic, social and environmental. This is because economic conditions alone are not enough to ensure the value of the company grows sustainably. Therefore, companies must balance economic performance with social and ecological performance. This study aims to prove the influence of eco-efficiency, green strategy, intellectual capital, and firm size on firm value. In addition, this study also aims to prove the moderating effect of intellectual capital on the influence of eco-efficiency and green strategy on firm value. The data in this study comes from the annual reports of companies listed on the Indonesia Stock Exchange during 2017 to 2022 which were selected using purposive sampling method. Data analysis was carried out using Moderated Regression Analysis (MRA). The results showed that firm value is influenced by eco-efficiency, intellectual capital, green strategy, and firm size. In addition, the results also show that intellectual capital can strengthen the influence of eco efficiency and green strategy on firm value. The implications of the results of this study confirm that company managers need to pay attention and focus not only on the company's economic performance but also social and environmental performance, so as to create maximum company value.